The Intrasubject Variability in the Acute Phase Protein (Orosomucoid) Levels and their Influenced by Breast Malignancy - Shatha Abd Al-jabbar; Rana M Hameed; Wesen Adel Mehdi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The major healthcare burden is breast cancer, screening services are expensive and difficult to organize, requiring major issues of administrative and quality control. however a potential biomarker that could help in the screening of the disease progress might improve the available routine mode of diagnosis. This study was aimed to examine the variability of Orosomucoid levels in breast cancer patients also to review the background documents on the state of the art of the scientific literature in this area of work.Materials and Methods: A cross sectional study was conduct on a breast cancer patients which were collected from oncology unit , Al-Hussein teaching Hospital in Kerbala / Iraq. Enzyme Linked Immunosorbent Assay system (ELISA) was performed using Sandwich method to measure the concentrations of serum Orosomucoid protein levels. Results: The primary stage of breast cancer was shown a wide spread range of the protein levels ( 95.4- 664.5 ng/ml) compared to the metastasis stage range (59.0- 376.3 ng/ml). The effect of disease duration and drug therapy also examine. Long term of duration of the disease with chemotherapy and/or hormonal therapy might decrease the level of protein, but, no significant differences were found.Conclusion: Since rosomucoid protein works as transporter, the protein may be used as an indication of the drug response due to decreased level in patients who were taking both chemotherapy and hormone therapy. Determination of serum rosomucoid protein could guide treating oncologist to have an idea to what extent the patients have response.